Dimethylation of eEF1A at Lysine 55 Plays a Key Role in the Regulation of eEF1A2 on Malignant Cell Functions of Acute Myeloid Leukemia - Shan Xiao MM; Yanping Wang MM; Yuwen Ma MM; Jue Liu MD; Can’e Tang MD; Aiping Deng MB; Chunxiang Fang MB (Technology in Cancer Research & Treatment, 2020)
Objective: This study aimed to explore whether eukaryotic translation elongation factor 1 alpha 2 affected cell proliferation, migration, and apoptosis via regulating the dimethylation of eukaryotic translation elongation factor 1 alpha at lysine 55 in acute myeloid leukemia. Methods: The expressions of eukaryotic translation elongation factor 1 alpha 2 and dimethylation of eukaryotic translation elongation factor 1 alpha at lysine 55 in acute myeloid leukemia cell lines and human normal bone marrow mononuclear cells (as control) were assessed. Control CRISPR-Cas9 lentivirus, eukaryotic translation elongation factor 1 alpha 2 knockout CRISPR-Cas9 lentivirus, vector plasmid, eukaryotic translation elongation factor 1 alpha 2 wild type overexpression plasmid, and eukaryotic translation elongation factor 1 alpha 2 with a K55R substitution overexpression plasmid were transfected into AML-193 and Kasumi-1 cells combined or alone, and were accordingly divided into 4 groups (Sgcontrol + vector group, SgeEF1A2 + vector group, SgeEF1A2 + eEF1A2 WT group, and SgeEFIA2 + eEF1A2 K55R group). Results: Eukaryotic translation elongation factor 1 alpha 2 and dimethylation of eukaryotic translation elongation factor 1 alpha at lysine 55 expressions were higher in AML-193, Kasumi-1, and KG-1 cell lines compared to the control. In AML-193 and Kasumi-1 cells, the knockout and compensated experiments revealed that eukaryotic translation elongation factor 1 alpha 2 promoted cell proliferation and migration but repressed apoptosis. Additionally, the knockout of eukaryotic translation elongation factor 1 alpha 2 decreased dimethylation of eukaryotic translation elongation factor 1 alpha at lysine 55 expression, meanwhile, eukaryotic translation elongation factor 1 alpha 2 wild type overexpression enhanced while eukaryotic translation elongation factor 1 alpha 2 with a K55R substitution overexpression did not influence the dimethylation of eukaryotic translation elongation factor 1 alpha at lysine 55 expression. Furthermore, eukaryotic translation elongation factor 1 alpha 2 wild type overexpression promoted cell proliferation, enhanced migration, and decreased apoptosis, but eukaryotic translation elongation factor 1 alpha 2 with a K55R substitution overexpression did not influence these cellular functions in AML-193 and Kasumi-1 cells, suggesting the implication of dimethylation of eukaryotic translation elongation factor 1 alpha at lysine 55 in eukaryotic translation elongation factor 1 alpha 2 mediated oncogenesis of acute myeloid leukemia. Conclusion: Eukaryotic translation elongation factor 1 alpha 2 and its dimethylated product may serve as therapeutic targets, and these findings may provide support for exploring novel strategies in acute myeloid leukemia treatment.